Hungarian Monitoring, 23 June 1988 . [Magyar rádiófigyelő], 1988. június 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Afghan prisoners of war question before UN - Soviet troop withdrawals from Afghanistan - British foreign minister in Prague Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee in session - Judges over-burdened with work - Political delegation in Finland - Várkonyi's statement on the Moscow summit - Exhibition in aid of Transylvanian Hungarians - John Paul II before his visit to Austria Külpolitika: - Afgán hadifoglyok ügye az ENSZ előtt - Szovjet csapatkivonulás Afganisztánból - A brit külügyminiszter Prágában Belpolitika: - MSZMP KB ülés - Túlterheltek a bírák - Politikai küldöttség Finnországban - Várkonyi nyilatkozata a moszkvai csúcsról - Kiállítás az erdélyi magyarok megsegítésére - II János Pál ausztriai látogatása előtt